A new dwarf species of Lycenchelys from western Antarctica with supplementary description of L. argentina (Teleostei, Zoarcidae) - Prokofiev, Artem M.; Kobyliansky, Stanislav G.; Orlov, Alexei M. (Zootaxa, 2026)
Lycenchelys cyanosoma sp. nov. is described from a single specimen collected off the South Orkney Islands at 370–375 m depth. It can be easily distinguished from all known congeners by its lowest total vertebral count (76), dorsal- and anal-fin ray counts (71 and 54, respectively); unusual bluish coloration with blackish head; and the following additional features in combination: body fully scaled except the predorsal area but vertical fins completely scaleless; absence of oral valve, pseudobranchs and pyloric caeca; upper lip with pronounced flange; and periproct surrounded by peculiar tentacle-like processes. The new species is probably the smallest member of the genus, having developed testes at 98 mm standard length. Lycenchelys argentina, a rare and poorly-known species with a variable morphology, is herein redescribed based on a new (fourth known) specimen; we discuss the limits of its morphological variation. Lycenchelys cyanosoma sp. nov. and L. argentina may represent vicariant species with upper and lower bathyal/abyssal range, respectively. The diagnostically valuable features and known distribution of all Antarctic and Subantarctic Lycenchelys species are presented.